La letra caníbal: Sobre Saba, Mariano. La letra caníbal. Textos dramáticos reunidos. Buenos Aires, Editorial EUDEBA/Proteatro, 2019, 220 pp. - Zucchi, Mariano (Saga. Revista de Letras, 2022)
Sobre Saba, Mariano. La letra caníbal. Textos dramáticos reunidos. Buenos Aires, Editorial EUDEBA/Proteatro, 2019, 220 pp.